(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Vitamin D, often called the "daylight vitamin," may be a basic supplement amid pregnancy, affecting both maternal wellbeing and fetal advancement. This article highlights the basic parts of vitamin D in calcium retention, resistant work, and hormonal control, emphasizing why its request increments amid development. Lack in pregnancy has been connected to complications such as gestational diabetes, preeclampsia, preterm birth, and impeded fetal skeletal development. In spite of its significance, numerous pregnant ladies stay insufficient due to restricted sun presentation, dietary inadequate, or metabolic variables. This audit synthesizes current prove on the benefits of satisfactory vitamin D levels, the dangers of lack, and commonsense suggestions for supplementation and daylight presentation to optimize pregnancy results. Guaranteeing adequate vitamin D admissions can be a straightforward however effective methodology for advancing more advantageous pregnancies and long-term child well-being. Pregnancy increments the request for vitamin D, and lack can lead to unfavorable results such as gestational diabetes, preeclampsia, preterm birth, and neonatal complications. This paper surveys the physiological parts of vitamin D, the results of insufficiency, and the significance of satisfactory supplementation or daylight introduction for ideal pregnancy results.